Dynamic thermal simulation of advanced natural ventilation in buildings: current and future usage, UK exemplar. (3rd July 2020) - Ji, Yingchun; Lee, Angela; Fernando, Terrence
ABSTRACT: This paper evaluates the use of advanced natural ventilation (ANV) strategies in a range of climatic conditions from four cities in the UK. A prototype ANV system was proposed to determine the most effective case in mitigating overheating. The case was then assessed under identical simulation conditions for all four ANV strategies. The overheating criteria used in the research include the single temperature criterion from CIBSE Guide A and the adaptive thermal comfort overheating criteria from BS EN 15251. Both the current and future 'Design Summer Year (DSY)' weather data were used to examine the thermal performances of the proposed design. The findings show that shading, night cooling and heavy weight structures (ceiling) were all useful in mitigating overheating, with night cooling being identified as the most effective measure. The work assessed the use of ANV in both current and future scenarios to quantify the limits of outdoor environmental conditions under which natural ventilation is an effective strategy for achieving thermal comfort. The adaptive thermal comfort overheating criteria were proved to be easier to meet compared with the CIBSE single temperature criterion. With the adaptive overheating criteria, the given design is predicted to not overheat until 2050 in London Heathrow; and for other places evaluated in the UK (Edinburgh, Manchester & Birmingham), the design passes these criteria. The Centre-in ANV strategies proved to be more effective than the Edge-in strategies for space cooling due to the extended structure thermal mass.